Survival of Acinetobacter spp. isolated from food to simulated gastrointestinal conditions - Monteiro, Ricardo Campos; Nascimento, Michel Santos Gomes do; Nascimento, Janaína dos Santos (Food Science and Technology, 2025)
In recent years, Acinetobacter isolates have frequently been obtained from foods of different origins, and the relevance of their presence and their role as a foodborne pathogen are rarely discussed. Surviving the passage through the gastrointestinal system is paramount to its intestinal colonization and, consequently, to triggering foodborne illnesses and other subsequent infections in the consumer. This work evaluated food isolates of Acinetobacter spp. (from ready-to-eat salads and goat milk) for their ability to survive in simulated gastrointestinal conditions. The isolates were exposed for 40 min at pH 2.0 in the presence of pepsin to simulate gastric conditions, followed by subsequent exposure to simulated intestinal fluid (with bile salts and trypsin) for 120 min. In general, reductions of 4.2–48.1% in viable counts of isolates were observed after exposure to the simulated gastrointestinal conditions. It is worth noting that six isolates showed a population reduction of less than 1 log CFU.mL-1. This study points out that some isolates of Acinetobacter spp. found in food could reach the intestine after ingestion of contaminated food, remaining viable and at high counts, therefore posing a potential risk as a food pathogen, being able to develop infections in consumers, especially in the most vulnerable ones.